Proceedings of the 2017 ITiCSE Conference on Working Group Reports 2018
DOI: 10.1145/3174781.3174785
|View full text |Cite
|
Sign up to set email alerts
|

"I know it when I see it" Perceptions of Code Quality

Abstract: Context. Code quality is a key issue in software development. The ability to develop high quality software is therefore a key learning goal of computing programs. However, there are no universally accepted measures to assess the quality of code and current standards are considered weak. Furthermore, there are many facets to code quality. Defining and explaining the concept of code quality is therefore a challenge faced by many educators. Objectives. In this working group, we investigated code quality as percei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 27 publications
0
27
0
Order By: Relevance
“…An ITiCSE working group [5] investigated which quality aspects are considered important by teachers, students and developers. In our study we zoom in on how teachers assess the quality of student code, focussing on data-, statement-and routine-level refactorings, which are most relevant for the programs that beginners write.…”
Section: Code Quality Terms and Definitionsmentioning
confidence: 99%
“…An ITiCSE working group [5] investigated which quality aspects are considered important by teachers, students and developers. In our study we zoom in on how teachers assess the quality of student code, focussing on data-, statement-and routine-level refactorings, which are most relevant for the programs that beginners write.…”
Section: Code Quality Terms and Definitionsmentioning
confidence: 99%
“…What constitutes good code is still an open question, but recent studies presentevidence that students, teachers, and professional developers usually associate good code to "readable" or "comprehensible" code[34]. Usually, one crucial component of readability is the structure of the code or its plan-composition strategy.…”
mentioning
confidence: 99%
“…Keuning et al identified several code quality issues in a large dataset of student-authored Java programs, as well as the undisciplined practices that led to these issues 3 . Through interviews, Börstler et al uncovered that students possess a low degree of skills and knowledge about code quality, concluding that code quality should be discussed more in CS education programs 1 . Other works focus on developing guidelines that help educators give code improvement feedback to students 4,2 . In the context of Scratch, the early works that explore code quality focus on identifying code quality problems 10,11,12,13 and applying program analysis tools to help educators better understand the quality of programs written by novice programmers 14,15,16 .…”
Section: Related Workmentioning
confidence: 99%
“…The CS Education research literature has established the importance of teaching software quality as part of the CS curriculum 1,2,3,4 . However, it remains subject to considerable debate whether the topic of software quality is appropriate for introductory learners.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation